Phytochemical studies on Stemona burkillii prain: Two new dihydrostemofoline alkaloids - Mungkornasawakul P. (2014)
Two new dihydrostemofoline alkaloids, 11(S),12(R)-dihydrostemofoline (3) and stemoburkilline (4), along with stemofoline (1) and 2′- hydroxystemofoline (2) have been isolated from a root extract of Stemona burkillii Prain. The structure and relative configuration of 3 have been determined via spectroscopic data and from comparison with synthetic 11(S),12(S)-dihydrostemofoline (5). The configuration of the exo-cyclic alkene group in 4 is tentively assigned as E on the basis of mechanistic considerations.